Public transport: a large scale fomite of methicillin-resistant Staphylococcus aureus - C. S., VinodKumar; Prasad, Sonika; Patil, Satish; Reddy V., Aditya; Jha, Ankita; Kumar K. G, Raghu .; V. L., Jayasimha; K. G., Basavarajappa (International Journal of Research in Medical Sciences, 2017)
Background: The role of public transport as reservoirs of antibiotic-resistant staphylococci was determined. Methods: 200 swabs were collected from 50 public buses (urban and rural) circulating in Davangere, Karnataka. Swabs collected were inoculated on Blood agar, Mannitol salt agar and MacConkey agar plates. After incubation for 24-48 hours, plates were examined for the growth of Staphylococcus aureus. Anti-microbial susceptibility test was performed using oxacillin 1ug disc to detect methicillin resistance as per CSLI guidelines. Results: Out of 40 Staphylococcus aureus isolated 35 isolates were resistant to more than two classes of antibiotics, hence multidrug resistant Staphylococcus aureus. Out of 35 MDR isolates, 18 were resistant to oxacillin and cefoxitin. Minimum inhibitory concentration test revealed that out of 35 MDR isolates, 18 isolates had MIC value of ≥ 4µg/ml. Conclusions: The recovery methicillin-resistant Staphylococcus aureus from public transport system implies a potential risk for transmission of these bacteria in community.